MLG713 : Discourse studies / Academy of Language Studies - UiTM, Academy of Language Studies (Universiti Teknologi MARA (UiTM), 2023)
The purpose of this course is to introduce students to fundamental concepts and methods in Discourse Analysis. Several approaches that describe and explain the structure and function of spoken, written and other types of discourses will be presented. Students will learn methods of discourse analysis and how to work with various kinds of research data, (documents, conversations, interviews and discourse in other media) derived from a range of contexts, including workplace and professional settings. Although the focus will be on the discourse of spoken and written English, the methods and general principles can be used to study discourse in other languages and in many different contexts.